Recommendations for the Use of Serious Games in Neurodegenerative Disorders: 2016 Delphi Panel - Manera, Valeria; Ben-Sadoun, Grégory; Aalbers, Teun; Agopyan, Hovannes; Askenazy, Florence; Benoit, Michel; Bensamoun, David; Bourgeois, Jérémy; Bredin, Jonathan; Bremond, Francois; Crispim-Junior, Carlos; David, Renaud; et al. (Frontiers in Psychology, 2017)
The use of Serious Games (SG) in the health domain is expanding. In the field of neurodegenerative disorders such as Alzheimer’s disease, SG are currently employed both to support and improve the assessment of different functional and cognitive abilities, and to provide alternative solutions for patients’ treatment, stimulation, and rehabilitation. As the field is quite young, recommendations on the use of SG in people with neurodegenerative disorders are still rare. In 2014 we proposed some initial recommendations (Robert et al., 2014). The aim of the present work was to update them, thanks to opinions gathered by experts in the field during an expert Delphi panel. Results confirmed that SG are adapted to elderly people with MCI and dementia, and can be employed for several purposes, including assessment, stimulation, and improving wellbeing, with some differences depending on the population (e.g., physical stimulation may be better suited for people with MCI). SG are more adapted for use with trained caregivers (both at home and in clinical settings), with a frequency ranging from 2 to 4 times a week. Importantly, the target of SG, their frequency of use and the context in which they are played depend on the SG typology (e.g., Exergame, cognitive game), and should be personalized with the help of a clinician.